Halloween kills [videorecording (DVD)] - Green, David Gordon, 1975-; Green, David Gordon, 1975-; Curtis, Jamie Lee, 1958-; Greer, Judy, 1975-; Matichak, Andi, 1994- (SDS, 2022)
Laurie Strode prepares to once again defend herself against Michael Myers after he breaks free from the burning cage where she had left him.